331 Adverse Childhood Experience and Sleep Quality in Adulthood. (3rd May 2021) - Bakour, Chighaf; Desch, Jill; Mansuri, Fahad; Schwartz, Skai W
Abstract: Introduction: Poor sleep quality, a risk factor for many negative health outcomes, may result from physical or emotional disturbance including chronic stress. Adverse childhood experiences (ACEs) have been linked with chronic stress, and may therefore be associated with poor sleep quality in adulthood. This study examines the longitudinal association between specific ACEs and the number of ACEs and sleep quality in adulthood. Methods: Using data from the National Longitudinal Study of Adolescent to Adult Health, we examined the association between ACEs and trouble falling asleep or staying asleep (rarely or never, sometimes, frequently) in waves 1 (age 12–18), 4 (age 24–32), and 5 (age 33–43). We examined ten ACEs (physical, sexual, or emotional abuse; neglect; parental death, incarceration, alcoholism, divorce or separation; foster home placement; poverty; and exposure to community violence) and the number of ACEs (0, 1, 2–3, 4+), using weighted logistic regression to calculate odds ratios and confidence intervals for each of the ACEs and ACE score and each of the outcomes after adjusting for relevant confounders. Results: The analysis included 12, 768 participants, 75.3% of whom experienced at least one ACE, including 14.7% who experienced 4 or more. Physical and emotional abuse were associated with frequent sleep complaints at waves 1, 4, and 5. Sexual abuse, neglect and community violence were associated with frequent complaints in two waves, while parental alcoholism, parental incarceration, and foster home placement were associated with frequent complaints in one wave. The number of ACEs experienced showed a dose-response association with frequent sleep complaints in wave 1 ([1 ACE: aOR=2.12 (1.16, 3.9), 2–3 ACEs: aOR=2.86 (1.70, 4.82), 4+ ACEs: aOR=4.17 (2.33, 7.48)], wave 4 [1 ACE: aOR=1.02 (0.77, 1.36); 2–3 ACEs: aOR= 1.66 (1.30, 2.10); 4+ ACEs: aOR=2.68 (1.99, 3.61) and in wave 5 [1 ACE: aOR=1.22 (0.93, 1.60)), 2–3 ACEs: aOR=1.42 (1.11, 1.81), 4+ ACEs: aOR=1.88 (1.40, 2.53)] Conclusion: Certain adverse childhood experiences such as physical, sexual, and emotional abuse and neglect have a lasting impact on sleep quality in adulthood, highlighting the need to mitigate their impact to prevent negative health outcomes associated with poor sleep quality Support (if any):